Smart computing and communication : second International Conference, SmartCom 2017, Shenzhen, China, December 10-12, 2017, Proceedings /: second International Conference, SmartCom 2017, Shenzhen, China, December 10-12, 2017, Proceedings. (2018) - Unknown
No abstract available